2020
DOI: 10.3390/app10030982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of new Seawater-based Mouth Rinse Versus Chlorhexidine 0.2% Reducing Plaque and Gingivitis Indexes. A Randomized Controlled Pilot Study

Abstract: For a long time, Chlorhexidine digluconate (CHX) has been considered the most used mouth-rinse for reducing plaque and gingivitis. Sea4® Encias is a new seawater-based mouth rinse with a similar action to CHX. Its prolonged use produces fewer side effects. This study compared the effects of two oral rinses: Chlorhexidine 0.20% and Sea 4® Encias (seawater) for reducing plaque and gingivitis indices. This double-blind crossover study recruited and monitored 93 volunteer dental students, hygienists and doctors fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Possible alternatives to chlorhexidine-based rinses include all natural polyherbal mouthwashes [43], probiotics [44], seawater-based mouthwash [45], or Beta-Cyclodextrin + Citrox [46]; however, all these solutions need more in-depth studies.…”
Section: Discussionmentioning
confidence: 99%
“…Possible alternatives to chlorhexidine-based rinses include all natural polyherbal mouthwashes [43], probiotics [44], seawater-based mouthwash [45], or Beta-Cyclodextrin + Citrox [46]; however, all these solutions need more in-depth studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of acute gingivitis, a related process could be found in the effect of 0.12 % CHX mouthwash after scaling and polishing, result in the reduction of clinical periodontal parameters such as PI, GI, and BOP compared to scaling and polishing alone [26]. The decline result may be due to CHX mouthwash's positive effect on plaque formation by its antibacterial activity, which greatly minimized and give controls for gingival inflammation in patients with poor oral hygiene [27]. The results showed no significant difference in the mean values of gingival indices between the chlorhexidine and OLE as mouthwashes [19].…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with other researchers' findings, on the effects of matrica mouthwash on bacterial plaque and gingival inflammation, which found that this mouthwash has a major impact on plaque accumulation, bleeding on probing, and gingival inflammation [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].In the treatment of chronic gingivitis, a related process could be found in the effect of 0.12 % CHX mouthwash after scaling and polishing, leading to a reduction in clinical periodontal parameters such as PI, GI, and BOP compared to scaling and polishing alone [26]. The decline may be due to CHX mouthwash's positive effect on plaque formation by its antibacterial activity, which greatly decreases and controls gingival inflammation in patients with poor oral hygiene [27].The results showed no significant difference in the mean values of gingival indices between the chlorhexidine and chamomile as mouthwashes [19]. Nevertheless, the result showed that the plaque inhibitory effects of 0.12 % CHX were slightly greater than that of 1% of chamomile, this may be because chlorhexidine has a wide spectrum of action, acting on bacteria that are Gram positive and Gram negative.…”
Section: Discussionmentioning
confidence: 99%